Accounting the Main Costs of Production in Farming and Legal Justification for their Compliance with International Standards (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this article, the author commented on the calculation of basic production costs on farms and the legal basis for their compliance with international standards.